Symptoms of wear HSS cutting tools in different wear stages - Paprocki, Marcin; Wygoda, Mateusz; Wyczesany, Paweł; Bazan, Patrycja (Manufacturing Technology Journal, 2021)
Planning a process of production, among other machining processes, is an important stage in the production of products. The developed machining process should allow production of parts with the planned dimensional accuracy and specified surface roughness. With reference to the above, the scope of the carried out theoretical work included determining the dependences between parameters of the drilling process, tool wear, as well as the impact of these parameters on the hole quality. The main aim of experimental research was to analyse cutting tools wear in various phases of tool usage. The research consisted in observation of metallographic microsections to analyse changes occurring in the drill bit microstructure. Then the microhardness was measured and in the next step the micro-hardness of the tested drills was statistically compared. Based on the results obtained, the percentage of wear for drill bits depending on microhardness was estimated taking into account the earlier esti-mated Percentable Production Cycle (PPC). This allowed determining the degree of wear and tear of drills by comparing the microstructure and microhardness between them. The aspects of cutting tool management are also discussed.
Keywords: cutting tool management; drill bit; wear; hole quality; microstructure; microhardness; percentable production cycle (PPC)